Paulo e o Judaísmo de seu tempo: O apóstolo dos gentios, de Israel, visto em uma "nova perspectiva" - Niebuhr, Karl-Wilhelm (Vox Scripturae - Revista Teológica Internacional, 2010)
The intention of the author is to try to answer two questions: 1) Where did the apostle Paul receive his major impulse in terms of formation: in Tarsus, in Asia Minor, or in Jerusalem, in the land of Israel. 2) What meaning and inplications bring to the exegesis the fact that Paul considers himself a pharisee. In other words, the author seeks to discern if Paul, before becoming a christian, found himself in the center of the judaic faith or on it´s borders. To answer these questions, the author presents and analizes, in a first step, the biographical testimonies of Paul´s life as we find it in his letters and how it´s testified in the book of Acts of the Apostles. A final and univocal answer concerning Tarsis or Jerusalem and how we should comprehend the pharisaism in Paul´s time the recent research of the later judaism hasn´t given us. Idependently of the asnwers, we can see a Paul deeply involved with his tradition and living of the faith, compromissed with the discernment of the will of God for his time. Here, the intention and work of Paul converge, according to the author, with ours today.
Keywords: Paul´s Biography; Paul as a pharisee; Christianism and Judaism; Primitive Judaism